Development and application of camelid molecular cytogenetic tools - Avila, Felipe; Das, Pranab J; Kutzler, Michelle; Owens, Elaine; Perelman, Polina; Rubes, Jiri; Hornak, Miroslav; Johnson, Warren E; Raudsepp, Terje (The Journal of heredity, 2014)
Cytogenetic chromosome maps offer molecular tools for genome analysis and clinical cytogenetics and are of particular importance for species with difficult karyotypes, such as camelids (2n = 74). Building on the available human-camel zoo-fluorescence in situ hybridization (FISH) data, we developed the first cytogenetic map for the alpaca (Lama pacos, LPA) genome by isolating and identifying 151 alpaca bacterial artificial chromosome (BAC) clones corresponding to 44 specific genes. The genes were mapped by FISH to 31 alpaca autosomes and the sex chromosomes; 11 chromosomes had 2 markers, which were ordered by dual-color FISH. The STS gene mapped to Xpter/Ypter, demarcating the pseudoautosomal region, whereas no markers were assigned to chromosomes 14, 21, 22, 28, and 36. The chromosome-specific markers were applied in clinical cytogenetics to identify LPA20, the major histocompatibility complex (MHC)-carrying chromosome, as a part of an autosomal translocation in a sterile male llama (Lama glama, LGL; 2n = 73,XY). FISH with LPAX BACs and LPA36 paints, as well as comparative genomic hybridization, were also used to investigate the origin of the minute chromosome, an abnormally small LPA36 in infertile female alpacas. This collection of cytogenetically mapped markers represents a new tool for camelid clinical cytogenetics and has applications for the improvement of the alpaca genome map and sequence assembly.
Keywords: Male; Sex Chromosomes; Chromosomes, Artificial, Bacterial; In Situ Hybridization, Fluorescence; Animals; genetické markery; Comparative Genomic Hybridization; FISH; mapování chromozomů; hybridizace in situ fluorescenční; BAC library; mužské pohlaví; Female; translocation; pohlavní chromozomy; Camelids, New World; Karyotyping; alpaca; karyotypizace; ženské pohlaví; cytogenetics; zvířata; srovnávací genomová hybridizace; umělé bakteriální chromozomy; Chromosome Mapping; minute chromosome; lamy; Genetic Markers